Aphrodisias papers 3 : the setting and quarries, mythological and other sculptural decoration, architectural development, Portico of Tiberius, and Tetrapylon : including the papers given at the Fourth International Aphrodisias Colloquium, held at King’s College, London on 14 March, 1992 : in memory of Kenan T. Erim (Ann Arbor, MI.)
224 s.